Exploring the relationship between metacognition and motivation in Peruvian basic education students - Yancachajlla-Quispe , Luis Iván; Rengifo-Ramírez , Sheyla Shericza; Farfán-Latorre , Marilú; Estrada-Araoz , Edwin Gustavo; Lavilla-Condori , Willian Gerardo; Lavilla-Condori , Mari Luz (Salud, Ciencia y Tecnología - Serie de Conferencias, 2024)
Introduction: Metacognition is essential in the teaching-learning process, as students who are aware of their own thinking processes tend to be more effective in acquiring knowledge and skills. Objective: To determine if there is a relationship between metacognition and motivation in Peruvian basic education students. Methods: Quantitative research, non-experimental design with correlational scope. The sample consisted of 130 students who responded to two questionnaires characterized by adequate metric properties. Results: Preliminarily, it was found that students applied metacognitive processes efficiently and their level of motivation was high. On the other hand, it was determined that the Kendall’s Tau b correlation coefficient for both variables was equal to 0.501 and the p-value was lower than the significance level (p<0.05). This implies that those students who were more aware and reflective about how they approached their academic activities, how they planned and executed learning strategies, tended to be more motivated in their studies. Conclusions: It was determined that there is a direct and significant relationship between metacognition and motivation in Peruvian basic education students. Therefore, it is suggested that teachers promote activities that develop self-reflection and awareness of thinking processes. This may include self-assessment exercises and learning journals